IMPLEMENTASI MODEL PROBLEM BASED LEARNING DENGAN MEDIA PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA MATERI Q.S AL-HUJURAT AYAT 13 DI SD NEGERI 050773 PANGKALAN SUSU - Ririn Kurnia Agustina Saragih (Journal of Community Devation, 2024)
The learning outcomes achieved by students so far have not been optimal, there are many problems that are the cause, from students' interest and motivation to learn to the choice of learning methods made by teachers. One of the efforts made to improve student learning outcomes is by implementing active learning strategies based on daily life problems, namely the PBL method with puzzle media which can facilitate students being active independently or in groups to gain mutual knowledge. This classroom action research aims to find out whether there is an increase in problem solving abilities on Q.S Al-Hujurat verse 13 material through the PBL method in class IV students at SD Negeri 050773 Pangkalan Susu. The subjects of this research were class IV students in semester 1 of 2024/2025. The research results were obtained as follows: In Cycle 2, 25 students (92%) completed their studies, higher than the success indicator, namely 80% of students completed their studies. In Cycle 2, students' problem solving abilities have reached the specified success indicator, namely 80%. This is supported by changes in actions taken by teachers and students where students no longer experience difficulties as in the first cycle meeting. These two activities are in the very good category. So it is concluded that learning by implementing PBL with puzzle media is able to increase the completeness of students' problem solving in the material of Surah Al-Hujurat verse 13.